مبدأ إستقلالية شرط التحكيم التجاري عن العقد - كيسي، زهيرة جيلالي عبدالقادر Kisi, Zahairah Jilali Abdulqader (المركز الجامعي أمين العقال الحاج موسى أق أخموك لتامنغست - معهد الحقوق والعلوم السياسية, 2015)
يعد أسلوب التحكيم التجاري من أهم الأساليب في المعاملات التجارية التي يلجأ إليها المتنازعون لحل نزاعاتهم بعيدا عن القضاء. ويتم ذلك بآليات معينة ومحددة هي إما شرط التحكيم او مشارطة التحكيم. غير أنه كثيرا ما يبطل أو يفسخ أو يلغي العقد مثار المنازعة الذي تضمن شرط التحكيم، مما قد يؤدي إلى إشكالية عويصة يحملها التساؤل الآتي؛ هل يفسخ أو يبطل شرط التحكيم تبعا للعقد ام يبقى قائما مستقلا عنه، على الرغم من فسخ العقد الأصلي أو إبطاله لأي سبب؟
Teh method of commercial arbitration is considered as one of teh most important methods in commercial transactions that teh disputants resorted to in order to settle there disputes far from of court. This can be done through certain and specific mechanisms which are either arbitration condition or arbitration stipulation. However, teh contract subject to teh dispute and which includes an arbitration condition is often invalidated or annulled or canceled, this may lead to a difficult problem carried in teh following question; -Will teh arbitration condition of teh contract be annulled or cancelled or will it remain valid and independent from it, in spite of teh dissolution or annulment of teh original contract for any reason?
Keywords: القوانين والتشريعات -- العقود القانونية -- التحكيم التجاري -- المعاملات التجارية -- المنازعات القانونية -- الجزائر -- المجتمع الجزائري -- مستخلصات الأبحاث -- الترجمة